Inklusi Keuangan Melalui Pembiayaan Syariah Dukung Percepatan Pembangunan Berkelanjutan (Studi Kasus pada PT. Sarana Multi Infrastruktur) - Lisa Yuni Lestari; M. Nanang Febrianto; Qomarul Huda (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
Development without considering environmental impacts threatens ecosystem sustainability. Islamic financial institutions become a catalyst for financing environmentally friendly projects. The purpose of this study is to identify financial inclusion through Islamic financing to accelerate sustainable development. Qualitative research with literature review, library data sources from books, journals, PT SMI internal reports, and relevant sources was conducted with content analysis. The findings of PT SMI as a financing catalyst with the main allocation of transition and renewable energy, waste management, mini-hydro electricity, and infrastructure projects, and multiplier effects have a social impact on job creation and poverty alleviation. The potential for Islamic financing of PT SMI is growing along with the increase in environmentally-based projects, regulations, support from national and international Islamic banks, and awareness of safe-haven assets. Islamic financing of PT SMI is effective in promoting sustainable development in Indonesia, supported by innovation, literacy, project risk mitigation management, human resource quality, and investor interest. The implications of this study are that Islamic financing of PT SMI plays a strategic role in impacting social, economic, and environmental aspects to strengthen the achievement of SDGs in Indonesia. Therefore, it is necessary to optimize and map funding allocation by prioritizing social and environmental projects that are in line with Islamic principles, SDGs achievements, and green taxonomy.